If (5 + 1)(6 ÷ 3)(8 − 5) = (3 + 3)x, then x =?

please explain how to do this very simply

i got up to 623= 36

36=6x

but how do you know what to do after that? how can you multiply 6 by x??

8 Answers

  • Do the simple math problems that are in parenthesis first. Which gives you 623=6x. Then multiply the problem that is before the equals sign. Which is 36=6x. Then to get x by itself you divide both sides by 6. Which leaves 6=x. So x is equal to 6.

  • First you do the parenthesis (this stuff:() I always began on the side where there is no "x." So 5+1= 6. 6/3=2. When two parenthesis are next to each other, that means to multiply. 8-5=3. 6x2x3= 36. So the left side equals 36. 3+3=6. 6 times what equals 36? X=6.

    Source(s): My very smart brain.
  • Solve each part that is in the parenthesis.

    5 + 1 = 6

    6 / 3 = 2

    8 - 5 = 3

    3 + 3 = 6

    Then multiply the first 3.

    6 2 3 = 36

    Get x by itself by dividing by 6.

    36 / 6 = 6

    x = 6

  • Everything in brackets is done individually first, and the brackets next to each other means multiplication.

    So this becomes 6 2 3 = 6 * x

    We can work each side out and that brings us to:

    36 = 6 * x

    Divide both sides of the equation by 6:

    6 = x

  • This implies 6 2 3 = 6x

    36 = 6x

    x = 36/6 = 6

  • (5 + 1)(6 ÷ 3)(8 − 5) = (3 + 3)x

    6 x 2 x 3 = 6x

    36 = 6x

    6x = 36

    x = 6

  • remember

    parenthesis

    division/ multiplication

    addition/subtraction

    so (6)(2)(3)=(6)x

    x =6

  • 6x2x3=36

    6xX=36

    then X=6

Leave a Reply

Your email address will not be published. Required fields are marked *

Related Posts